POTRET INTEGRASI ISLAM DAN BUDAYA NUSANTARA DI ERA WALISONGO - Adib, Hamdan (Risâlah, Jurnal Pendidikan dan Studi Islam, 2021)
Abstract Until now this form is still a lot of cultural forms in question because it is not the original innate religion of Islam in Arabia. The existing culture in Indonesia, some have stated and acknowledged that culture is a feature of Islam in Indonesia by some others being opposed because there is no historical or Naqli argument to prove it So in this study, it will be explained about the study of integration in this archipelago which began in the Walisongo era and has existed until now. The method used in this research is qualitative library research where researchers will conduct a study into various literatures related to Islam and Culture in the archipelago from various documents. The results found are Islam in Java where the Javanese community still maintains tahlilan, slametan and the culture attached to the community which has fruited its value from what was originally a Hindu-Buddhist pattern turned into Islamic, besides that the pesantren education system also colors this integration, Islam in Sumatra is supported by three forces, namely pesantren, markets and palaces, and Islam in eastern Indonesia was carried out by students from one of the walisngo in Java. Through this research, it will be found both theoretically regarding the integration of Islam and the culture of the archipelago as well as the practices that occur